A blind spot in correct naming latency analyses. Issue 1 (17th February 2017) - Oppenheim, Gary M.
ABSTRACT: Speech errors and naming latencies provide two complementary sets of behavioural data for understanding language production processes. A recent analytical trend—applied to intact and impaired production alike—highlights a link between specific features of correct picture naming latency distributions and the retrieval processes thought to underlie them. Although chronometric approaches to language production typically consider correct response times in isolation, adequately accounting for their distributions in error-prone situations requires also considering the errors that sometimes censor them. In this paper, I illustrate by simulation how excluding incorrect word retrievals predictably alters observed distributions of correct naming latencies. To the extent that naming errors impose a stochastic deadline on successful production, their censoring should tend to reduce the mean, variance, and skew of observed latencies for correct responses, relative to the uncensored underlying distribution.